2021
DOI: 10.3390/cells11010068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TCR Repertoire by High-Throughput Sequencing Indicates the Feature of T Cell Immune Response after SARS-CoV-2 Infection

Abstract: Coronavirus disease 2019 (COVID-19) is a global infectious disease caused by the SARS-CoV-2 coronavirus. T cells play an essential role in the body’s fighting against the virus invasion, and the T cell receptor (TCR) is crucial in T cell-mediated virus recognition and clearance. However, little has been known about the features of T cell response in convalescent COVID-19 patients. In this study, using 5′RACE technology and PacBio sequencing, we analyzed the TCR repertoire of COVID-19 patients after recovery fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Single-cell sequencing has been used to compare the TCR repertoire between COVID-19 patients and healthy controls, observing a very significant reduction in TCR clones diversity and disease-related changes in V and J gene usage, with less gene subfamilies and preferential V-J combinations used in COVID-19 patients. Those findings have been confirmed by others [ 137 , 138 ], specifying that the preferential V(D)J sequences only exist in the convalescent patients [ 137 ].…”
Section: Tcr and Infectious Diseasessupporting
confidence: 74%
See 2 more Smart Citations
“…Single-cell sequencing has been used to compare the TCR repertoire between COVID-19 patients and healthy controls, observing a very significant reduction in TCR clones diversity and disease-related changes in V and J gene usage, with less gene subfamilies and preferential V-J combinations used in COVID-19 patients. Those findings have been confirmed by others [ 137 , 138 ], specifying that the preferential V(D)J sequences only exist in the convalescent patients [ 137 ].…”
Section: Tcr and Infectious Diseasessupporting
confidence: 74%
“…Some shared TCRs sequences appeared 2 weeks after convalescence and persisted up to 6 months, suggesting these clones might represent the T-memory phenotype associated with the disease [ 137 ]. The same observation has been reported in a population of antibody-seronegative convalescent individuals with asymptomatic and mild COVID-19, where the presence of SARS-CoV-2-specific polyfunctional stem-like memory phenotype T-cells in the peripheral blood suggests that an effective T-cell response may exert sufficient immune protection against the virus, even in the absence of neutralizing antibodies [ 127 , 139 ].…”
Section: Tcr and Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, T cell receptor (TCR) genes such as TRAV8-4, TRAV26-2, TRBV28, TRBV30 and TRBV4-2 were also upregulated after rAdVV vaccination. TRAV8-4 genes found be expanded in COVID-19 convalescent 43 , thus it could be reflecting that rAdVV vaccination have spike specific NKT cell activation. In case of mRNA (PoV2/3) vaccines based upon upregulated genes, pathway analysis revealed that NKT cells should be positively regulating activation of other cell types including platelets activation and aggregation, cell adhesion, cellular defence response, chemokine signalling pathways, and infection of human immunodeficiency virus 1.…”
Section: Altered Gene Expression and Signalling Pathways After Radvv ...mentioning
confidence: 92%
“…Serologic analysis discovered that protective adaptive immune responses of anti-SARS-CoV-2 antibodies and specific memory B and T cell responses caused by natural SARS-CoV-2 infection may last for at least 6-8 months after the onset of symptoms, 28 and the diversity of the immune repertoire in convalescent patients with COVID-19 is associated with outcomes. 29 Although for most of the people infected with COVID-19, the symptoms are mild, even asymptomatic, 30,31 the long-term effect of COVID-19 infection on the immune system still attracts tremendous public attention. Here, we discovered characteristic pan-immune repertoire alterations, like lymphopenia, reduced unique CDR3 number and reduced diversity, together with the…”
Section: Introductionmentioning
confidence: 99%